Identification and evaluation of sources of resistance to kalahasti malady in groundnut - and G.J. MOSES, P. HARINATH NAIDU (Indian Phytopathology, 2002)
A severe nematode disease of groundnut (Arachis hypogaea), popularly called 'Kalahasti malady' and caused by the nematode Tylenchorhynchus brevilineatus has been prevalent since 1976 in certain parts of Andhra Pradesh. A total of 39 groundnut genotypes, including three control varieties were screened for resistance to the nematode disease at Srikalahasti, Andhra Pradesh during 1992-94. Three test genotypes, TCGS-307, TCGS-313 and TCGS-320 and a resistant check variety TPT-3 exhibited resistant reaction to the nematode disease with a disease score of 2.0. Among the three genotypes TCGS-313 and TCGS-320 gave maximum pod yields of 3.18 and 3.15 t/ha, and grain yield of 2.11 and 2.21 t/ha, respectively. Two genotypes, TCGS-305 and TCGS-306 among the 17 moderately resistant genotypes (2.5 to 3.0 disease score) recorded highest pod yields of 3.27 and 3.24 t/ha, and grain yields of 2.16 and 2.27 t/ha, respectively. Thirteen genotypes, including the susceptible control JL-24, showed susceptible reactionto the disease (3.5 to 4.0 disease score) while five genotypes showed highly susceptible reaction to the disease (4.35 to 5.0 disease score).